Citrus Rootstock Breeding and Selection - Forner-Giner, María A.; Continella, Alberto; Grosser, J. D. (Springer, 2021)
The use of rootstocks in the evolution of citriculture has played a key role in the success of citrus industries worldwide. Rootstock has a strong influence on yield, fruit quality and tree size, and can provide tolerance to abiotic and biotic stresses. Dominant and emerging rootstocks has been described, reporting their characteristics that allow their utilization in relation to prevailing conditions of soil, climate and disease. Aim of this chapter is also to provide current and future citrus rootstock breeders a practical guide that will facilitate efforts to develop improved rootstocks capable to solve many current issues of citrus production and fruit quality worldwide.